Antisocial behavior and crime: contributions of developmental and evaluation research to prevention and intervention - Bliesener, Thomas; Lösel, Friedrich (Hogrefe, 2012)
In honor of Friedrich Lösel / Thomas Bliesener, Andreas Beelmann and Mark Stemmler -- Developmental courses of antisocial behaviors. Environmental, genetic and epigenetic influences on the developmental origins of aggression and other disruptive behaviors / Richard E Tremblay -- Subtypes of aggressive behaviors: etiologies, development, and consequences / Frank Vitaro and Mara Brendgen -- Developmental sequence and pathways towards serious delinquency and substance use / Rolf Loeber, Helene Raskin White and Jeffery D Burke -- Persistent juvenile offenders / Thomas Bliesener -- Risk and protective factors in antisocial behaviors. Protective and promotive factors in the development of offending / David P Farrington and Maria M Ttofi -- Family factors in the development of antisocial behavior / Lea Pulkkinen -- Social sources of crime propensity: a study of the collective efficacy of families, schools, and neighborhoods / Per-Olof H Wikström -- Media consumption and violence in schools / Franz Streng -- Crime prevention, offender treatment, and rehabilitation. The scientific foundation of prevention: the status quo and future challenges for developmental crime prevention crime prevention / Andreas Beelmann -- Measuring conflict of interest in prevention and intervention research: a feasibility study / Manuel Eisner and David Humphreys -- Effective interventions for juvenile offenders: using meta-analysis to bridge from research to practice / Mark W Lipsey -- Offender resistance policing (ODP): less prison and more evidence in rehabilitating offenders / Lawrence W Sherman -- Risk management and criminal justice. Violence risk assessment: things that I have learned so far / David J Cooke -- Comprehensive risk management instruments for serious and violent young offenders: challenges and advantages / Raymond R Carrado -- Forensic psychological assessment in the criminal justice system:development and perspectives in Germany / Rudolf Egg -- Young offenders and legal competencies / Ronald Roesch -- Research methods in development criminology. The development of delinquent behavior: variable- and person-oriented methods of analysis / Alexander von Eye, Richard M Lerner, Jacqueline V Lerner and Edmond P Bowers -- Latent growth curve modeling and the study of problem behavior in girls / Mark Stemmler and Anne C Peterson -- Evaluating a national program: effects of No Child Left Behind on math achievement in the United States / Thomas D Cook, Manyee Wong, and Peter Steiner -- Principles of symmetry in evaluation research with implications for offender treatment / Werner W Wittmann